The Effects of Combination of Range Motion and Deep Breathing Exercise on Pain in Post-Orthopedic Surgery Patients - Sasongko, Hery; Sukartini, Tintin; Wahyuni, Erna Dwi; Putra, Made Mahaguna (Indonesian Journal of Medicine, 2019)
Background: Broken bones can cause soft tissue edema, bleeding in the muscles and joints, tendon rupture, damage to nerve tissue and damage to the vasculer and surgery are ways that are carried out to restore the movement function of extremitas and the impact that occurs due to these actions is pain. Acute pain is still found in postoperative non-pathological fracture patients who have received analgesic ketorolac.Subjects and Method: This was a quasy experiment study conducted at Dr. Soetomo Hospital, Surabaya, East Java. A sample of 46 patients post orthopedic surgery was selected for study by purposive sampling. The dependent variable was pain. The independent variables were range of motion and deep breathing exercises. Pain was measured by visual analog scale (VAS). The data were analyzed by t-test.Results: After treatment, pain level in the intervention group (mean = 2.43; SD = 1.41) was lower than the control group (mean= 3.48; SD= 1.38) with p= 0.014.Discussion: Combination of range of motion and deep breathing relaxation therapy effective to reduce pain among post orthopedic surgery patients.Correspondence: Hery Sasongko. Masters Program in Nursing, Universitas Airlangga. Email: herysasongko.ners@gmail.com.Indonesian Journal of Medicine (2019), 4(1): 46-53https://doi.org/10.26911/theijmed.2019.04.01.08